Simulasi Dan Analisis Performansi Vehicular Ad Hoc Network (VANET) Dengan Menggunakan Protokol Routing Berbasis Posisi Di Pekanbaru - Eryzal SP Siregar; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Intellegent Transportation System (ITS) is a system for solving transportation problems that offers safety, efficiency, and comfort in traffic. Implementation of Vehicular Ad Hoc Network (VANET) that is part of a development of ITS. VANET can be a new innovation in the world of technology that allows to communicate vehicle between vehicle and vehicles with infrastructure. VANET has high node mobility and a routing protocol is required to support VANET communications. In this paper, one of the protocols used are position based routing protocols is Greedy Perimeter Stateless Protocols (GPSR). Density of vehicles in Pekanbaru city make the main problem for implementing VANET communication. VANET communications will result of Packet Delivery Ratio (PDR), end to end delay and routing overhead. In this research, scenario used are 50 node scenario and speed scenario at 10 m/s. The simulation result of VANET with GPSR routing protocol based position shows PDR, end to end delay and data routing value are 99.4860%; 0.0057 seconds dan 6756 packet.Keyword :Intellegent Transportation System, Vehicular ad hoc Network, Greedy Perimeter Stateless Routing